Radiotherapy-Induced Lung Cancer Risk in Breast Cancer Patients: A Retrospective Comparison of Hypofractionated and Standard Fractionated 3D-CRT Treatments - Alessia D’Anna; Giuseppe Stella; Elisa Bonanno; Giuseppina Rita Borzì; Nina Cavalli; Andrea Girlando; Anna Maria Gueli; Martina Pace; Lucia Zirone; Carmelo Marino (Applied Sciences)
Breast-conserving surgery followed by external beam Radiotherapy (RT) is a standard approach for early-stage Breast Cancer (BC). This retrospective study aims to determine the risk of RT-induced lung cancer for both standard and hypofractionated treatments. Fifty-eight Sicilian women treated at Humanitas Istituto Clinico Catanese (Misterbianco, Italy) between 2015 and 2021 with standard fractionated 3D-CRT (50 Gy in 2 Gy/fraction) were included. All treatment plans were designed using a hypofractionated schedule (42.56 Gy in 2.66 Gy/fraction). An Eclipse™ plug-in script was developed using the Eclipse Scripting Application Programming Interface (ESAPI) to extract patient and treatment data from the Treatment Planning System and compute Organ At Risk (OAR) volume, Organ Equivalent Dose (OED), Excess Absolute Risk (EAR), and Lifetime Attributable Risk (LAR) using the Schneider Mechanistic Model and reference data from regional populations, A-bomb survivors, and patients with Hodgkin’s Disease (HD). The OED distributions exhibited a statistically significant shift toward higher values in standard fractionated plans (p < 0.01, one-tailed paired Student’s t-test), leading to increased EAR and LAR. These results indicate that hypofractionated treatment may lower the risk of radiation-induced lung cancer. The feasibility of a priori risk estimation was evaluated by integrating the script into the TPS, allowing rapid comparison of SF and HF plans during planning.